IMPACT OF DEVELOPMENT PROGRAMS ON EMPOWERMENT OF RURAL WOMEN IN JIJEL - Assia Lifa (International Journal of Innovative Technologies in Social Science, 2024)
This research document aims to highlight the role of rural development programs approved by the State in order to restore development to the rural world and to empower rural women through various programs and policies which enabled them to exercise their development role, despite the great challenges they encounter. The rural renewal policy has changed the lives of rural women, since thanks to the support funds allocated by the State, which make it possible to encourage rural women to develop and create private investment projects in various fields, traditional industries, agricultural and other industries. The role of rural Algerian women in this support has become apparent. In order to integrate women in the rural world, the State has set up local rural development projects with the objective of developing and improving the standard of living of the rural world. And develop women in particular. These projects have contributed to developing the work of women in agricultural and artisanal activities. We have noticed that rural women can support themselves and their communities and help build thriving rural economies if they have the opportunity to produce.